Membrane Domains as Signaling Centers in Macrophages and T-Cells: From Concepts to Experiments - Rentero, Carles; Magenau, Astrid; Williamson, David; Tedla, Nicodemus; Gaus, Katharina (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2008)
Engagement of surface receptors on immune cells triggers intracellular signaling cascades and downstream activation responses. To function in immune responses, activation of macrophages and T-cells must be finely controlled and regulated. Curiously, different extracellular signals often trigger the same signaling pathways with common elements yet result in vastly different outcomes. It has thus been hypothesized that it is the organization of signal transduction processes in space and time that ultimately determines cell responses. The idea that membrane domains on the cell surface could influence the behavior of signaling proteins, and thus act as ‘signaling organizers’ has merged the fields of membrane biology and signal transduction. It is now known that lipids and proteins are not homogeneously distributed in cell membranes giving rise to specialized membrane domains or lipid rafts. Different concepts of membrane organization put forward lipid-lipid, lipid-protein or membrane-skeleton interactions as the underlying principle for domain formation. This review discusses experimental approaches, and their limitations, that have been used to test these concepts. We further review the role of lipid domains during phagocytosis by macrophages and T-cell activation. Although there are substantial differences between these two cell types, there is strong evidence that receptor clustering induces the coalescence of lipid domains that play an integrated role in signal transduction.
Keywords: protein clustering